Financing Decisions: An Approach for the 21st Century - Gaytán Cortés, Juan (Mercados y Negocios, 2024)
Businesses are the essential engine of development in a nation’s economy. By improving their profitability and competitiveness, they reduce the risk of failure and boost GDP growth and job creation. This, in turn, encourages investment and promotes a more equitable income distribution, contributing to society’s general well-being (Romero, 2013).